Factors influencing customer to switch mobile service provider: A case study at UiTM KB / Siti Nurani Zulkfli ... [et al.] - Zulkfli, Siti Nurani; Abd Razak, Nor Fatihah; Che Yusof, Nur Syaliza Hanim; Nordin, Noor Ilanie; Salleh, Aisyah Wahyuna; Che Apandi, Nur Ain Mardiah; Shikh Mohd Noor, Siti Nur Auni Husna (Unit Penerbitan UiTM Kelantan, 2020)
Malaysia's telecommunications services industry has grown significantly over the last few years especially in mobile service providers. Hence, mobile service provider have great challenges on how to retain their consumer, since there were so many elements that might cause customers to switch their mobile service providers. This study aimed to explore the effect element of price, sales promotion, peer and family influence and customer service in attracting user to switch mobile service providers. A set of questionnaire was used to collect data from 280 respondents using a simple random sampling technique. Reliability analysis, correlation analysis, multiple linear regression were conducted by using IBM SPSS. The findings showed that price and customer service has a significant effect on the customer switching. Pearson correlation analysis was tested to determine the relationship between all the factors that influence consumer switching. The result reveals that customer switching has highest correlation with price but lowest correlation with peer and family influence. This study will beneficial to mobile service providers to develop new marketing strategy in order to maintain their customers.